1999
DOI: 10.1063/1.57797
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo analysis of a monolithic interconnected module with a back surface reflector

Abstract: NOTICERecently, the photon Monte Carlo code, RACER-X, was modified to include wavelength dependent absorption coefficients and indices of refraction. This work was done in an effort to increase the code's capabilities to be more applicable to a wider range of problems.These new features make RACER-X useful for analyzing devices like Monolithic Interconnected Modules (MIMs) which have etched surface features and incorporates a back surface reflector (BSR) for spectral controL A series of calculations were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The first surface of the device exposed to incident light is a featureless plane. As a result, light trapping due to the presence of grid fingers , interconnects, or etch trenches common to a standard single-junction MIM [7] is eliminated at the device surface. The planar surface also facilitates the direct deposition or attachment of a first surface filter to enhance transmission of above-bandgap photons and minimize transmission of below-bandgap photons.…”
Section: Ingaasmimmentioning
confidence: 99%
See 1 more Smart Citation
“…The first surface of the device exposed to incident light is a featureless plane. As a result, light trapping due to the presence of grid fingers , interconnects, or etch trenches common to a standard single-junction MIM [7] is eliminated at the device surface. The planar surface also facilitates the direct deposition or attachment of a first surface filter to enhance transmission of above-bandgap photons and minimize transmission of below-bandgap photons.…”
Section: Ingaasmimmentioning
confidence: 99%
“…Monte Carlo photonic simulation was conducted and demonstrated that any disturbance from a planar first surface seriously degraded the spectral control performance of the MIM [7]. The interdigitated design, which incorporates v-groove trenches for electrical isolation (as does the conventional MIM design) as well as dovetail trenches for the LCL contact grid, suffered the greatest degradation in optical performance due to this effect.…”
Section: Ingaasmimmentioning
confidence: 99%
“…• The high angular dispersion of incident photons, together with non-specular reflections, lead to the potential for optical frustration [2], (i.e. trapping and multiple internal reflections within the high refraction index layers of the diode/filter).…”
Section: Tpv Spectral Control Challengesmentioning
confidence: 99%
“…grids, busbars, and gaps between diodes) 2. angular and polarization dependent radiator emissivity (i.e., non-Lambertian), 3. angular and polarization dependent front surface filter reflectivity 4. finite separation between radiator and diode which alters the angular dispersion 5. cavity edge leakage or sidewall absorption These non-ideal cavity attributes complicate the photon recuperation. In general, advanced numerical techniques such as Monte Carlo and photon ray tracing are needed to quantify the impact of these processes on TPV performance [2,5].…”
Section: Figures Of Merit For Tpv Spectral Controlmentioning
confidence: 99%
“…Recent Monte-Carlo photonic modeling, being presented at this conference [9], suggests that the processing techniques used can have a significant effect on the amount -..-.. -. 'Ofpl~fihs thaf can be-recuperated 'at-tie 'radiator: Four 'areas of particular-interest are the specukddiffused reflectance of the BS~light trapping due to surface features (i.e., isolation trenches), the reflectance of the electrical metailization at the metalsemiconductor interface, and IR absorption in the anti-reflective coating.…”
Section: Mim Design and Structurementioning
confidence: 99%